2021
DOI: 10.1002/cpz1.76
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Deafness and Recent Advances Towards Restoring Hearing Loss

Abstract: Congenital hearing loss is the most common birth defect, estimated to affect 2‐3 in every 1000 births. Currently there is no cure for hearing loss. Treatment options are limited to hearing aids for mild and moderate cases, and cochlear implants for severe and profound hearing loss. Here we provide a literature overview of the environmental and genetic causes of congenital hearing loss, common animal models and methods used for hearing research, as well as recent advances towards developing therapies to treat c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 383 publications
0
16
0
4
Order By: Relevance
“…The global threat to human health posed by pathogenic flaviviruses is likely to continue for the foreseeable future [46], necessitating further progress in understanding virusinduced pathologies. ZIKV now joins several pathogens whose exposure to the gestating fetus correlates with congenital hearing loss after birth [47,48]. Knowing whether infection of the peripheral auditory system in utero could underlie some aspects of the ensuing hearing loss is necessary for choosing appropriate therapeutic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The global threat to human health posed by pathogenic flaviviruses is likely to continue for the foreseeable future [46], necessitating further progress in understanding virusinduced pathologies. ZIKV now joins several pathogens whose exposure to the gestating fetus correlates with congenital hearing loss after birth [47,48]. Knowing whether infection of the peripheral auditory system in utero could underlie some aspects of the ensuing hearing loss is necessary for choosing appropriate therapeutic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Several protocols have been devised to direct hPSCs into inner ear HCs and neuron-like cells. The efficiency, reproducibility, and scalability of these protocols are enhanced by incorporating knowledge of inner ear development [13,17,18,[67][68][69][70]. Early studies on the transplantation of hPSCs-derived otic progenitors have been successful in certain animal models [103], but the hearing was transiently restored, and long-term cell survival continues to be a major challenge.…”
Section: Modeling Inner Ear Disorders: 2d and 3d Cell Culturementioning
confidence: 99%
“…The major achievements in disease modeling using a hiPSC-derived inner ear for genetic SNHL include the genes MYO7A, MYO15, and MERRF in HCs [70,89,90], and GJB2 and SLC26A4 (Pendred syndrome) in SCs [106,[123][124][125] (Table 2). These studies have defined the molecular mechanisms involving each gene and showed the cellular effects of each mutation.…”
Section: Clinical Trials In Inner Ear Disordersmentioning
confidence: 99%
“…3 In the United States, in the year 2021 the disorder was found in 2-3 cases per 1000 live births. 4 The proportion of congenital deafness in children aged 24-59 months in Indonesia based on a survey in the year 2019 was 0.11%. 5 Appropriate management of patients with congenital deafness by establishing an early diagnosis and early intervention is very important to reduce the medical and social burden on patients, families, and communities, and also to improve patients' quality of life.…”
Section: Introductionmentioning
confidence: 99%